O audiovisual na perspectiva da complexidade: reflexões a partir da produção da websérie documental “autorais e diversos” - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The theme of this dissertation research reveals knowledge about audiovisual as a field of the Creative Industry, where the general objective seeks to understand the process of audiovisual production in the context of original music and from the perspective of complexity theory, through the analysis of the web series "Autorais e Diversos", which portrays the production of original music in the municipality of Ijuí-RS. Thus, the aim is to analyze the process of producing the web series based on the principles of complexity, verifying potential elements in this production process to consider the documentary as a place of memory and possibility of social representation, as well as pondering about the complex documentary and the representation of original music. The methodology used was participatory, where the universe of musicians was entered and the reality of audiovisual production as well as the context portrayed in the web series were experienced in practice. As a result, it was verified that complex thinking, by considering diversity and the need for debate, can contribute to the development of audiovisual as a means of representation and memory for musicians and artists, as well as to the expansion of the art of originality. Despite the challenges in audiovisual production, this form of art can bring new and real elements in an attractive way to the audience.
Keywords: Recursos audiovisuais; Comunicação; Direitos autorais - Canções e música; Comunicação de massa e música; Indústria cultural; Audiovisual resources; Communication; CNPQ::CIENCIAS SOCIAIS APLICADAS